Modelo deposicional de carbonatos albianos da Formação Quissamã: análise faciológica, diagenética e estratigráfica de um campo de óleo na porção meridional da Bacia de Campos - Favoreto, Julia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Albian carbonate rocks of the Quissamã and Outeiro formations were analysed in an oil field (16 km2) of the Quissamã Reservoir, Campos Basin (Rio de Janeiro, Southeastern Brazil). According to several integrated petrographic and stratigraphic procedures (neural network) applied to cores of four wells and geophysical profiles of other 24 wells, including the software Petrel® 2012 (Schlumberger), it was possible to recognize lithofacies (along with diagenetic and permo-porosity properties), electrofacies, cyclic successions, giving support for stratigraphic correlations, stratigraphic sequences analysis, maps of facies proportions for each sequence and respective paleoenvironmental models. Six lithofacies were defined for the Quissamã Formation, mainly grainstones and packstones (rare wackestones) with carbonate grains such as ooids, oncoids, peloids and some bioclasts (mollusks, echinoids and benthonic microfossils). Successions of peloidal/bioclastic packstones to grainstones correspond to typical shallowing upwards high frequency cycles. The Outeiro Formation has three lithofacies composed of mudstones and wackestones, with gradual increase of more distal planktonic microfossils (mainly foraminifers). The diagenetic history of the rocks encompassed, during the eodiagenesis, micritization, mechanic compactation, dissolution, cementation (fringe, mosaic and sintaxial) and, during the mesodiagenesis, chemical compactation and blocky cementation in fractures. The whole studied interval presents some maximum flooding and maximum regressive surfaces, which were defined as boundaries, respectively, for the medium and low frequency successions, the latter equivalent to five stratigraphic sequences. The present work corroborates previous interpretations that the Quissamã Formation was originated in a shallow carbonate ramp-like platform with several ooids bars parallel to the coast. Therefore, the other facies of the formation (mainly...

Rochas carbonáticas albianas das formações Quissamã e Outeiro foram estudadas num campo de petróleo de 16 km2 do Reservatório Quissamã, Bacia de Campos (RJ). De acordo com diversos procedimentos petrográficos e estratigráficos integrados (redes neurais) aplicados a testemunhos de quatro poços e perfis geofísicos de outros 24 poços, incluindo a utilização do software Petrel® 2012 (Schlumberger), foram reconhecidas litofácies (abrangendo também características diagenéticas e de permo-porosidade), eletrofácies, sucessões cíclicas, dando suporte para correlações estratigráficas, análises no âmbito da estratigrafia de sequências, confecção de mapas de proporção de fácies referentes a cada sequência e, finalmente, modelos dos respectivos paleoambientes da área de estudo. Para a Formação Quissamã foram definidas seis litofácies, principalmente grainstones e packstones (raros wackestones) com grãos carbonáticos compostos por ooides, oncoides, peloides e alguns bioclastos (moluscos, equinoides, microfósseis bentônicos). Sucessões de packstones peloidais/bioclásticos para grainstones representam típicos ciclos de alta frequência da passagem de paleoambientes deposicionais relativamente profundos/calmos para rasos/com maior energia. A Formação Outeiro apresenta três litofácies compostas por mudstones e wackestones, com gradual aumento de microfósseis de organismos planctônicos marinhos mais distais (principalmente foraminíferos). A história diagenética das rochas envolveu, na eodiagênese, processos de micritização, compactação mecânica, dissolução, cimentação (franja, mosaico e sintaxial) e, na mesodiagênese, compactação química e cimentação blocosa em fraturas. Todo o intervalo estudado apresenta superfícies de inundação máxima e de regressão máxima, as quais foram definidas como limites, respectivamente, para sucessões de média e baixa frequência, as últimas equivalentes...
Keywords: Geology, Stratigraphic; Geologia estratigráfica; Carbonatos; Bacias sedimentares; Facies (Geologia); Geologia estratigráfica - Cretáceo; Paleoambiente; Campos, Bacia de (RJ)